The effect of instructional video drama on students’ perceptions on the observance of Islamic ethics: an experimental approach - Ibrahim, Ahmad Abdullahi; Syed Hassan, Sharifah Sariah; Hashim, Sulaiman (Contemporary Research Center, 2016)
Islamic education. Such objective is difficult to be achieved through the adoption of traditional approach of teaching. Therefore, this study aims to investigate the effect of instructional video drama in instilling Islamic ethics among secondary school students in Kano state of Nigeria. 60 students from School for Arabic Studies were randomly selected and assigned into control and experimental group. The researcher adopted lottery method of random sampling to select the subjects for the experimentation. A survey using adapted questionnaire measuring students’ willingness towards the observance of Islamic was administered to the students of both control and experimental group. For the triangulation purpose, one on one interview was carried out to support the quantitative result. The data was analyzed using independents sample t-test to find out statistically significant difference of the mean score between the two groups. Moreover, inductive analysis technique was employed to analyse interview. The result shows corroboration between the two data sets (survey and interview). It is revealed that students from experimental group have higher willingness towards the observance of Islamic ethics than those in the control group. Finally, this research serves as benchmark for integrating video drama in teaching Islamic studies in general and Islamic ethic in particular